Investigation on Resonant Vibration Performances of Fe‐Doped BiScO3–PbTiO3 Ceramics in High‐Temperature Environment. Issue 10 (1st July 2015) - Wu, Jingen; Yu, Yang; Li, Xiaotian; Gao, Xiangyu; Dong, Shuxiang
Abstract : The high‐temperature performance of a series of Fe‐doped BiScO3 ‐PbTiO3 (BSPT) piezoelectric ceramics at the morphotropic phase boundary was investigated. The effects of different Fe contents on the piezoceramics were assessed with regard to variations in structure, morphology, dielectric properties, piezoelectric properties, and high‐temperature resonant vibration. X‐ray diffraction (XRD) results indicated that the Fe‐doped BSPT ceramics show a single perovskite structure and that the c / a ratio undergoes a slight increase with increasing Fe concentrations. It was also found that, as the proportion of Fe in the ceramics was increased, the grain size was enlarged somewhat, the dielectric loss (tan δ) decreased, the mechanical quality factor ( Q m ) was gradually improved, and the Curie temperature ( T C ) was increased from 426°C to approximately 460°C. Despite these complex effects, it was evident that Fe doping can improve the high‐temperature resonant vibration performance of BSPT ceramics, and that these materials exhibit stable resonant vibration velocities at temperatures as high as 225°C. Our results indicate that Fe‐doped BSPT ceramics have the potential to be used as piezoelectric power devices intended for high‐temperature environments.